Risk Analysis of Business Continuity Plan in Light Steel Company Using ISO 31000 Framework - Andry, Johanes Fernandes; Christianto, Kevin; Purnomo, Yunianto; Lee, Francka Sakti (Universitas Bina Darma, 2024)
Light Steel Company is an industry engaged in manufacturing, has adopted technology and has a data center. The purpose of this study is to provide a guide and strategy for preventing risks and actions to minimize and overcome risks that can be used and implemented, so that the company's business processes can continue to run sustainably. This study uses Business Continuity Plan (BCP) using ISO 31000. Data collection is used by an interviewing employee who works at this organization. The analysis shows there are 15 possible risks that will hinder the operation of Light Steel companies based on the risk level high, medium, and low categories. High risk level is 26.7%, there are 4 possible risks, namely R05 (Loss of spare parts), R06 (Unscheduled maintenance and care for trucks and equipment spare parts), R10 (Server down) and R012 (Network connection problems). Medium risk level is 26.7%, there are 4 possible risks, namely R02 (flood), R07 (Cybercrime), R08 (Hacking), and R011 (Sudden power outage). Finally for low risk level is 46.6%, there are 7 possible risks, namely R01 (Earthquake), R03 (Dust), R04 (Fire), R09 (Abuse of access rights), R13 (Overheat), R14 (Data Corrupt), and R15 (Virus Attack, Malware).